Alkoxylation for Surfactant Productions: Toward the Continuous Reactors - Tesser, Riccardo; Russo, Vincenzo; Santacesaria, Elio; Hreczuch, Wiesław; Di Serio, Martino (Frontiers in Chemical Engineering, 2020)
Alkoxylation is surely an important reaction as it is industrially utilized to produce surfactants. The actual technology is to convert ethylene oxide/propylene oxide with a long-chained alcohol, catalyzed by a homogeneous catalyst . Traditionally, the operation is conducted in semi-batch, systems characterized by a low productivity. As the demand of surfactants production is increasing, it is natural to shift to a continuous process. In the present review article, the most recent efforts dealing with the alkoxylation processes in continuous are reported, analyzing critically the results reported in both the scientific and patent literature.